大學生健康老化多元創意教學課程之成效研究：從健康覺察到行動 Effects of Multiple-Creative Teaching Strategies in a Healthy Aging Course for College Students: From Health Self-Awareness to Action - 陳毓璟 Stephanie Yu-Ching Chen (National Taiwan Normal University, 2019)
本研究運用行為改變的跨理論模式和健康自我管理計畫方法，再融入代間學習的策略發展成健康老化多元創意課程，並評量此課程的立即學習成效和延宕效果。研究對象為選修老化相關課程之大學生 35 人。本研究採質量並重的混合研究方法，運用單組前測、後測及後後測的研究設計之量化分析，以及透過課程觀察紀錄和學生反思報告之質性資料分析來記錄學習歷程與成效。研究結果發現，健康老化多元創意教學對學生健康老化知識、態度和健康行為的學習影響皆具有正面顯著的影響，且經過 1 年後，不論知識、態度或行為，其正面成效 不僅持續，且部分指標有愈來愈佳之趨勢。除學生提出多增加代間互動之課程建議外，本研究針對未來課程設計與研究亦提出建議。 This study used a trans-theoretical model of behavioral change and evaluated a health self-management program. The teaching strategy of intergenerational learning was integrated into a multicultural healthy aging curriculum, and immediate learning and delay effects were evaluated. In total, 35 college students studied an elective course on elder health care. The research design combined qualitative and quantitative methods, adopting a single group for pretest, posttest, and follow-up and performing co-inspection of qualitative data of observation records and students' reflective reports to explore the learning process and effects. The results demonstrated that multiple-creative teaching strategies in a healthy aging course had a mostly positive and significant effect on students' health knowledge, attitudes, and health behaviors. After a year, positive results for health knowledge, attitudes, and behaviors were not only sustained but increased. In addition to students' suggestions on how to increase intergenerational interaction, this study provides suggestions for subsequent course and research design.